Partisipasi Masyarakat dalam Meningkatkan Pembangunan di Kampung Kalitoko Kabupaten Raja Ampat - Rumbiak, Nikanor; Muhammad Ali; salmawati, salmawati (Universitas Muhammadiyah Sorong, 2024)
Community participation is very necessary in encouraging accelerated development. Development will not run optimally without community participation, namely active participation from the community. This research aims to describe and analyze the problems that occur in community participation in development in Kalitoko Village, Teluk Mayalibit District, Raja Ampat Regency. This research was conducted in Kalitoko village, Teluk Mayalibit District, Raja Ampat Regency. The aim of this research is to determine the level of community participation in development in Kalitoko village, factors that influence community participation in development, what work programs are being implemented in Kalitoko village. . This research method uses a qualitative approach with a field research type, namely data collection, using interviews, observation and documentation. The results of this research show that the form of community participation in development in Kalitoko village has improved quite a lot, because the community provides assistance in the form of energy and ideas. This shows that community participation in Kalitoko village is active in a series of activities, namely that the community is always present in the development process, always present at deliberations and always present at meetings.